Implementasi Teori Multiple Inteligences dalam Pengembangan Program Bilingual di MAK Al Hikmah 2 Brebes - Fadhlurrohman, Muhammad; Untung, Slamet (Jurnal Ilmu Pendidikan Muhammadiyah Kramat Jati, 2025)
This study aims to analyze the implementation of Multiple Intelligences theory in the development of a bilingual program at Madrasah Aliyah Keagamaan (MAK) Al Hikmah 2 Brebes. MAK Al Hikmah 2 is an educational institution specializing in the in-depth study of religious subjects and the development of Arabic and English language skills through an intensive bilingual program. The Multiple Intelligences theory, developed by Howard Gardner, emphasizes that every individual possesses various forms of intelligence that can be optimized within an educational context. This research employs a qualitative approach using a case study method, involving observation, interviews, and document analysis. The findings indicate that the implementation of Multiple Intelligences theory in the bilingual program at MAK Al Hikmah 2 has successfully enhanced students' proficiency in both languages and developed their intellectual potentials holistically. Moreover, this program positively impacts the strengthening of religious character and the ability to read classical Islamic texts. These findings contribute significantly to the development of a bilingual education model based on Multiple Intelligences theory in religious educational institutions.